Mechanical and electrical characterization of CVD-grown graphene transferred on chalcogenide Ge2Sb2Te5 layers. (June 2018) - D'Arrigo, G.; Christian, M.; Morandi, V.; Favaro, G.; Bongiorno, C.; Mio, A.M.; Russo, M.; Sitta, A.; Calabretta, M.; Sciuto, A.; Piccinini, E.; D'Urso, L.; et al.
Abstract: In the present work, we investigate some mechanical and electrical properties of a Chemical Vapor Deposition (CVD)-grown graphene layer transferred on 50 nm-thick Ge2 Sb2 Te5 chalcogenide and discuss the possible application of graphene as a scaled contact replacing metal lines in phase-change memory devices. At first, the graphene-chalcogenide interface was extensively investigated. The expected chemical composition was confirmed by means of Electron Energy Loss Spectrometry (EELS), and the absence of bond distortions in the chalcogenide layer after graphene transfer was proved through Raman spectroscopy. The latter evidenced also the presence of defects, further confirmed by Transmission Electron Microscopy (TEM) investigations. The quality of the contact stack was evaluated by means of the adhesion among layers and by the sheet resistance of the layers themselves. Scratch tests and numerical simulations revealed a stress distribution compatible with a failure of the interface where the graphene layer features a 2 %-void. Next, the contact resistance proved an effective good Ohmic quality with a high graphene sheet resistance, about 1400 Ohm/square, which suggests that a better optimized transfer process should be applied to reduce it more than one order of magnitude. Graphical abstract: Image